Desenho e análise da rede de coprodução acadêmica de um departamento da universidade federal de São Carlos (UFSCar) - Bertho, Patricia Mayumi Mito (Universidade Federal de São Carlos, 2025)
This research investigates the academic co-production network of professors from the Department of Production Engineering at the Federal University of São Carlos (UFSCar), covering the period from 2000 to 2024, identifying collaboration patterns, the positions occupied by actors, and the influence of the distribution of scientific and social capital on the network’s configuration. The research is grounded in Social Network Analysis (SNA) and collaboration networks, articulated with Pierre Bourdieu’s theory of the scientific field. Data were collected from the Lattes Platform profiles of active faculty members of the department and include journal articles classified as individual productions, co-productions among active department members, co-productions with graduate students, and co-productions with other collaborators. For the analysis, network metrics such as degree and betweenness centrality were applied using UCINET software, while the network visualization was developed with Gephi. The results indicate that co-production involving graduate students is the most significant, followed by collaborations among DEP faculty members. Professors with greater scientific capital occupy central positions in the network, benefiting from increased visibility and access to strategic collaborations, while peripheral actors show lower levels of integration. It is concluded that the network results from the interaction between structural and relational factors and that the integration of SNA, collaboration network analysis, and Bourdieu’s theoretical framework enables a critical understanding of the dynamics of scientific production within the department.
Design and analysis of the academic co-production network of a department at the Federal University of São Carlos (UFSCar)
Keywords: Análise de redes sociais; Coprodução acadêmica; Redes sociais; Redes de colaboração científica; Teoria do campo; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DA PRODUCAO; 4. Educação de Qualidade